The Urgency of Management Functions in Improving the Quality of Education Services in Public Senior High Schools 1 Biak - Hermanu Iriawan; Wilda Sasmita; Muhammad Rusdi (Program Pascasarjana Universitas Negeri Makassar, 2019)
The quality of education services is a